Chiral Extensions of the MSSM - Karateev, Denis (My University, 2012)
This thesis is based on the paper [1]. We present the construction and analysis of supersymmetric models. We begin by giving a short description of the Minimal Supersymmetric Standard Model (MSSM) and pointing out its two main problems. Motivated to resolve them we construct a class of MSSM extensions characterized by a fully chiral field content (no -terms) and no baryon or lepton number violating terms in the superpotential due to an extra U0(1) gauge symmetry. The minimal models consist of the usual matter sector with family dependent U0(1) charges, six Higgs weak doublets, and four charged singlets required to give masses to the Higgsinos, cancel anomalies and allow for commensurate charges. These models are characterized by a discrete set of solutions for the charges. The models with right handed neutrino superfields are also presented. As a different issue we briefly discuss the SUSY breaking mechanism in gauge mediation scenario, where we show how an extra gaugino ~ Z0 can be used to mediated SUSY breaking from the Hidden Sector. Analysing the models, we discuss their general features, e.g. classical vacuum, CPviolation, Electro-Weak symmetry breaking and running coupling constants. In the end we investigate the decays of Z and Z0 -bosons and study in detail experimental constraints on Flavour Changing processes.
Keywords: Fysik; Physical Sciences